1962
DOI: 10.1111/j.1423-0410.1962.tb03226.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of A and B Antigens by Transfused Group O Erythrocytes

Abstract: Summary Group O donor cells recovered from the circulation of group A or B recipients are agglutinable by a proportion of group O sera, and sometimes by a smaller proportion of group B or A sera, showing that they have taken up A or B substance. The uptake of antigen takes about a fortnight to reach a maximum level and no uptake of antigen could be shown following incubation of group O cells with group A1 blood or plasma for 41 hrs. at 37° C in vitro. Résumé Les érythrocytes de donneurs de groupe O récupéré de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…Reported methods of patient preparation for major ABO-incompatible transplant where the re cipient has ABO antibodies directed against donor red cells include: whole blood or occurring during a severe delayed hemolytic transfusion reaction. It supports the obser vation that IgG anti-A and anti-B induce spherocytosis and in vivo agglutination [23,24], It also suggests that the earliest observ able morphologic change in delayed hemo lysis is the appearance of bite cells, and dem onstrates the formation of intercellular erythrocyte bridges, probably comprised of cell membrane containing IgG.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Reported methods of patient preparation for major ABO-incompatible transplant where the re cipient has ABO antibodies directed against donor red cells include: whole blood or occurring during a severe delayed hemolytic transfusion reaction. It supports the obser vation that IgG anti-A and anti-B induce spherocytosis and in vivo agglutination [23,24], It also suggests that the earliest observ able morphologic change in delayed hemo lysis is the appearance of bite cells, and dem onstrates the formation of intercellular erythrocyte bridges, probably comprised of cell membrane containing IgG.…”
Section: Discussionsupporting
confidence: 57%
“…The red cell aggre gates are thought to be loose and easily dis rupted [22], producing the transient devel opment of the striking mixed field reaction. In addition, it is possible that some of the patient's own group O red cells were tran siently incorporated into these agglutinins since it has been shown that group O red cells can passively absorb A and B substance and be induced to agglutinate with the ap propriate antiserum [23]. Although we could not document that this phenomenon occurred in our patient, he did receive 5 lit ers of group AB fresh frozen plasma, four units of group AB red cells, and group AB bone marrow, containing substantial amounts of A and B substances.…”
Section: Discussionmentioning
confidence: 99%
“…The observation in 1962 by Renton and Hancock [13] that A and B substances in plasma can be taken up by circulating O cells can now be explained by our finding that these substances, like Lea and Leb, are probably glycosphingolipids. Like cells which have adsorbed A or B substance in vivo [13], cells which are transformed in vitro by lipid fractions are rarely ag glutinated by the anti-A (or anti-B) formed by B (or A) subjects.…”
Section: Resultsmentioning
confidence: 70%
“…Because, like Lewis antigens, A and B [13] and A1Leb [3,18] are adsorbed onto red cells in vivo, it seemed likely that these antigens in plasma would be glycosphingolipids. We now describe the finding of A and B and AjLeb in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of an investigation into the uptake of A and B antigen by transfused group O erythro cytes, for example, no difficulty was encountered in separating group O cells from the circulation of a group A patient who had received only 500 ml of group 0 blood forty-eight days previously [2].…”
Section: Discussionmentioning
confidence: 99%